2016
DOI: 10.19082/2670
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Bone Morphogenetic Protein 7 in Ankylosing Spondylitis and its association with disease activity and radiographic damage

Abstract: IntroductionFusion of joints as well as intervertebral spaces by the formation of bony spurs appearing as syndesmophytes and osteophytes are the hallmark of spondyloarthropathies which accounts for disability. The aim of this study was to assess the serum level of bone morphogenetic protein (BMP)-7 in ankylosing spondylitis and its relationship with disease activity and the radiographic damage.MethodsThis longitudinal case control study was conducted in Ain Shams University Hospitals (Egypt). A total of 55 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In some studies, the difference in their results was reported for the differences in the disease stages and the severity of bone injuries. 40,46 In conclusion, the BMP8A CNVs seem to play no role in susceptibility to AS in Iranian population. Although it might not be regulated by CNVs, BMP8a may have a role in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In some studies, the difference in their results was reported for the differences in the disease stages and the severity of bone injuries. 40,46 In conclusion, the BMP8A CNVs seem to play no role in susceptibility to AS in Iranian population. Although it might not be regulated by CNVs, BMP8a may have a role in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 78%
“…It seems, based on the evidence, that our results of gene expression can be dependent on the induction time, the condition, and the phase or stage of the disease. In some studies, the difference in their results was reported for the differences in the disease stages and the severity of bone injuries …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, BMP-2 is an active and important member which can independently or synergistically with other signaling pathways like the Wnt/β-catenin pathway, enhance osteoblast differentiation and bone formation [ 10 , 11 ]. Data regarding the level of these proteins in AS patients are incompatible; however, most of them show higher levels of these proteins in patients compared to healthy controls [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, BMP-2 is an active and important member which can independently or synergistically with other signaling pathways like the Wnt/β-catenin pathway, enhance osteoblast differentiation and bone formation [10,9]. Data regarding the level of these proteins in AS patients are incompatible; however, most of them show higher levels of these proteins in patients compared to healthy controls [11,12].…”
Section: Introductionmentioning
confidence: 99%